Characterization of online high dynamic range imaging for laser-driven ion beam diagnostics using visible light - Englbrecht Franz; Balling Felix; Rösch Thomas Federico; Würl Matthias; Lindner Florian Hans; Parodi Katia; Schreiber Jörg (Current Directions in Biomedical Engineering, 2017)
Laser-driven acceleration of particle beams is an emerging modality under research for biomedical applications. The spatially resolved diagnostics of laser-accelerated proton bunches is crucial for their application. The RadEye detector, featuring up to 10 cm x 5 cm area of online complementary metal-oxide-semiconductor (CMOS) detector made of 48 μm pixels, is established for x-ray, proton and ion beam diagnostics. We exploit the usually undesired ‘Image lag’ phenomenon of incomplete pixel reset to generate 2D-images with a larger dynamic range than the single frame range of 12-bit. Using 532 nm laser pulses and computer simulations for single-slit diffraction, calibration factors to stack multiple readouts were successfully derived to quantitatively reconstruct spatial information about an optical beam and hence extend the dynamic range of the detector compared to a single frame. The final goal is focus quantification for a permanent magnet quadrupole system for protons and terawatt (TW-class) laser focus diagnostics.